Phenotypic Analysis of Mutants of Ergosterol Biosynthesis Genes (ERG3 and ERG4) in the Red Yeast Xanthophyllomyces dendrorhous - Venegas, Maximiliano; Barahona, Salvador; González, Ana María; Sepúlveda, Dionisia; Zúñiga, Gustavo E.; Baeza, Marcelo; Cifuentes, Víctor; Alcaíno, Jennifer (Frontiers in Microbiology, 2020)
Xanthophyllomyces dendrorhous synthesizes astaxanthin, a carotenoid used in aquaculture. Astaxanthin is synthesized from metabolites of the mevalonate pathway, which are also precursors for sterols biosynthesis. The interruption of the CYP61 gene, which is involved in the synthesis of ergosterol (mutant CBS.cyp61-), resulted in a phenotype that overproduces carotenoids due to the activation of the SREBP pathway. In this work, we constructed other mutants of ergosterol biosynthesis in this yeast to evaluate whether they have the same phenotype as mutant CBS.cyp61-. By bioinformatic analysis, the ERG3 and ERG4 genes of X. dendrorhous were identified, and each gene was deleted in the wild-type strain. Mutants CBS.Δerg3 and CBS.Δerg4 did not produce ergosterol; CBS.Δerg3 primarily accumulated episterol, and CBS.Δerg4 primarily accumulated ergosta-5,7,22,24(28)-tetraenol. The transcription levels of the HMGS gene of the mevalonate pathway were evaluated by RT-qPCR, which showed a slight increase in CBS.Δerg4, but the transcription levels were still 10-fold lower than in strain CBS.cyp61-. Both CBS.Δerg3 and CBS.Δerg4 did not overproduce carotenoids, even though they do not produce ergosterol. Thus, the results of this study indicate that the absence of ergosterol does not activate the SREBP pathway in X. dendrorhous, but rather it depends on other alterations in sterol composition.